Modulating Macrophage Phenotype by Sustained MicroRNA Delivery Improves Host‐Implant Integration. Issue 3 (18th December 2019) - Lin, Junquan; Mohamed, Ibrahim; Lin, Po Hen; Shirahama, Hitomi; Milbreta, Ulla; Sieow, Je Lin; Peng, Yanfen; Bugiani, Marianna; Wong, Siew Cheng; Levinson, Howard; Chew, Sing Yian
Abstract: Biomedical implant failure due to the host's response remains a challenging problem. In particular, the formation of the fibrous capsule is a common barrier for the normal function of implants. Currently, there is mounting evidence indicating that the polarization state of macrophages plays an important role in effecting the foreign body reaction (FBR). This opens up a potential avenue for improving host‐implant integration. Here, electrospun poly(caprolactone‐ co ‐ethyl ethylene phosphate) nanofiber scaffolds are utilized to deliver microRNAs (miRs) to induce macrophage polarization and modulate FBR. Specifically, C57BL/6 mice that are treated with M2‐inducing miRs, Let‐7c and miR‐124, display relatively thinner fibrous capsule formation around the scaffolds at both Week 2 and 4, as compared to treatment with M1‐inducing miR, Anti‐Let‐7c. Histological analysis shows that the density of blood vessels in the scaffolds are the highest in miR‐124 treatment group, followed by Anti‐Let‐7c and Let‐7c treatment groups. Based on immunohistochemical quantifications, these miR‐encapsulated nanofiber scaffolds are useful for localized and sustained delivery of functional miRs and are able to modulate macrophage polarization during the first 2 weeks of implantation to result in significant alteration in host‐implant integration at longer time points. Abstract : Biofunctional microRNA‐encapsulated electrospun scaffolds regulate macrophage polarization and fibrous capsule formation upon subcutaneous implantation in mice. Specifically, M2 macrophage‐inducing microRNAs reduce fibrous capsule thickness while M1 macrophage‐inducing microRNAs result in an increased fibrous encapsulation of the implanted scaffold.